Enforcing Service Stability for WebAssembly Extended Reality Workloads at the Edge: A Quality of Service Aware Orchestration Framework - Jardim, Gustavo Spadotto; Silvestre, Bruno Oliveira; Cardoso, Kleber Vieira; Pires, Matheus; Corrêa, Sand Luz; Verdi, Fábio; Both, Cristiano Bonato (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Modern Extended Reality (XR) applications require stringent low-latency processing that often exceeds the capabilities of end-user devices, necessitating computation offloading to the network edge, which is addressed by Multi-access Edge Computing (MEC). However, the resource-constrained and heterogeneous nature of MEC poses significant orchestration challenges. In this context, traditional distributed application orchestration and load balancing methods can lead to severe Quality of Service (QoS) degradation for immersive applications. This work addresses this gap by proposing a QoS-aware orchestration framework designed specifically for distributed WebAssembly (Wasm) computer vision workloads. We first provide a comparative analysis of Wasm runtimes against Docker containers, demonstrating that Wasm significantly reduces the memory footprint while maintaining comparable inference performance. Taking advantage of these benefits, we evaluate a custom orchestration mechanism that uses active QoS probing to enforce strict performance thresholds. The results reveal that the proposed orchestrator successfully enforces service stability. This evaluation shows that combining lightweight runtimes with active QoS-aware orchestration is a prerequisite for viable XR applications at the edge.